Study of the association of seventeen single nucleotide polymorphisms and their haplotypes in the TNF-α, IL-2, IL-4 and IL-10 genes with the antibody response to inactivated Japanese encephalitis vaccine - Yufeng Yao; Xiuwen Xu; Yaheng Li; Xiaona Wang; Huijuan Yang; Jun Chen; Shuyuan Liu; Yan Deng; Zhimei Zhao; Qiongzhou Yin; Mingbo Sun; Li Shi (Taylor & Francis Group, 2020)
To investigate whether the TNF-α, IL-2, IL-4 and IL-10 genes contribute to variations in vaccine-induced immune responses after immunization with the inactivated Japanese encephalitis vaccine (IJEV), a total of 369 individuals who received the IJEV were enrolled. Based on Japanese encephalitis virus (JEV) neutralization antibodies (NAbs), the individuals were divided into seropositive (SP) and seronegative (SN) groups. Then, 17 SNPs in the TNF-α, IL-2, IL-4 and IL-10 genes were genotyped using the TaqMan method. Although there was no association of the TNF-α, IL-2, IL-4 and IL-10 genes with JEV seropositivity triggered by JEV vaccination when all the individuals in the SP and SN groups were compared, differences were observed in a subgroup analysis. In the male group, rs2243291 in the IL-4 gene showed a difference between the JEV SP and SN groups with the overdominant model (P = .045), and the C/G genotypes conferred more JEV seropositivity (OR = 1.87; 95% CI: 1.01-3.49); the CT genotype of rs3093726 in the TNF-α gene showed higher JEV NAbs geometric mean titer (GMT) than the TT genotype (P = .018, CT: 1.677 ± 0.144 vs TT: 1.271 ± 0.039). Furthermore, the rs1800629 genotype in the TNF-α gene and the rs1800896 genotype in the IL-10 gene exhibited a trend of association with JEV seropositivity in the female group, but the difference was not significant. The present study suggested that the polymorphisms in the cytokine genes could be associated with sex-specific JEV NAbs seroconversion. However, more samples should be studied, and further functional verification should be performed.